Spread of Rotylenchulus reniformis in an Arkansas Cotton Field Over a Four-Year Period - Monfort, W S (Journal of nematology, 2008)
Rotylenchulus reniformis was first detected in a single grid (100 m(2)) in May 2001 in a cotton field in Ashley County, AR, that was being utilized to evaluate the utility of grid-sampling for detection of Meloidogyne incognita. A total of 512 grids were sampled in the 6-ha field in the spring and fall for four years (2001 - 2004), nematode populations were determined for each grid, and nematode population density maps were constructed utilizing Global Positioning Systems and Geographic Information Systems. In May 2001, R. reniformis population density in the single grid where it was detected was 6,364 juveniles and adult reniform nematodes/500 cm(3) soil. By the end of the first year (October 2001), the nematode was found in 17 of the 512 plots with population densities ranging from 682 to 10,909 nematodes/500 cm(3) soil. Over the course of the 4-yr period, reniform nematode incidence increased to 107 of 512 plots, with population density ranging from 227 to 32,727 nematodes/500 cm(3) soil. Reniform nematode spread could be explained by the direction of tillage and water flow in the low end of the field. Highest population densities were observed in the areas of the field with soil types ranging from 54% to 60% silt fraction. In addition to R. reniformis, Meloidogyne incognita was commonly detected in many of the grids, and Tylenchorhynchus spp., Helicotylenchus spp., Paratrichodorus minor and Hoplolaimus magnistylus were detected occasionally